Best practices in anti-corruption in the Philippines - United Nations Development Programme; Australian Agency for International Development (Quezon City Career Executive Service Board, 2005)
"On the whole, this compilation represents an exhaustive documentation of the most outstanding practices of anti-corruption initiatives in the country involving various sectors of society. They draw up the critical building blocks to thriving efforts in combating graft. They provide the framework for other entities and individuals to pattern their anti-corruption agenda on. While the concepts and ideas embedded in these efforts do not exactly guarantee success in their replication in other anti-corruption crusades, it is important--and reassuring--to note that they are born out of actual experiences of those involved."--Preface.
Forewords -- Preface -- Chapter 1. Anti-corruption agencies -- Chapter 2. Civil society -- Chapter 3. Government agencies.
Keywords: Political corruption -- Philippines; Misconduct in office -- Philippines; Philippines -- Politics and government